(untitled) (Biological Sciences - PJSIR, 2001)
Roosting ecology of Red Junglefowl (Gallus gal/us spadiceus) was studied in oil palm plantation at Sungai Sedu Estate, Selangor, Malaysia. The data were collected by observing the Red Junglefowls directly and with the aid of radio telemetry. Student’s t-test was used to examine the differences of roosting activities between males. Pearson correlation analysis was done to examine the relationship between environmental factors and roosting behaviour. The results showed that the Red Junglefowl preferred horizontal frond for roosting at night. In choosing a suitable roosting site, it climbed and walked on the branch step by step and frequently changed branches and trees from time to time. The roosting height varied between 4 to 12 rn, However, hen with chicks roosted lower than other birds. The Red Junglefowl departed 7 min earlier than sunrise and roosted 2 min before sunset. The average time spent on roosting on tree was about 11 h 47 min Generally, the female went to roost earlier than the male and the male departed earlier than the female.